Educação física com crianças de seis meses a dois anos de idade : práticas produzidas no cotidiano de um CMEI de Vitória/ES - Rosa, Amanda De Pianti (2014)
The work analyzes the practices produced by children and the Teacher in the daily life of the Physical Education classes at a Children’s Education Municipal Center (CMEI) in the city of Vitória/ES. It uses the Studies with Everyday Life as a theoretical-methodological assumption and uses the data produced in different sources, such as, iconographic records, children’s and the Physical Education Teacher narratives and also the participant observation, systematized in a field journal. The data produced demonstrate that the children tactically acted before the strategies proposed by the Teacher, standing out a reception esthetics, that is, they did not passively consume the cultural goods – games, toys, playful activities – which they were offered, because they attributed their singular marks, arising from their interests, needs and possibilities to act. The playful activities that involved the material handling and the exploitation of environments favored the children’s autonomous and creative actions, which although very young, were considered the authors of the activities developed. It was found that, even in the initial groups of Children Education, it is possible to consider the children as culture producers and as leading figures of their socialization process. However, to do so, it is necessary to focus the uses and appropriations of the games, the playful activities and the toys in the Children’s Education daily life, manifesting, above all, through their body narratives. The research also concludes that the routine is a dimension that needs to be reconfigured, in the sense of the act of care does not become a single form of action contemplated when dealing with little children.